Ulcer‐free survival days and ulcer healing in patients with diabetic foot ulcers: A prospective cohort study. Issue 6 (19th August 2019) - Akturk, Afram; van Netten, Jaap J.; Scheer, Rene; Vermeer, Marloes; van Baal, Jeff G.
Abstract: Healing rates may not give a complete indication of the effectiveness and management of diabetic foot ulcers because of high recurrence rates. The most important outcome for patients is remaining ulcer‐free; however, this has hardly been investigated. The aim of our study was to prospectively investigate ulcer‐free survival days and ulcer healing in patients with diabetic foot ulcers. This was a prospective cohort study of all referrals to our diabetic foot expertise centre from December 2014 to April 2017. Outcomes were determined after a minimum follow‐up period of 12 months. Primary outcomes were ulcer‐free survival days and 12‐month healing percentages. Predictors for ulcer‐free survival days and healing were investigated in multivariate analyses. A total of 158 patients were included. Median ulcer‐free survival days in the healed group were 233 days (interquartile range [IQR] 121‐312) and 131 days (IQR 0–298) in the overall population. The healing rate at 12‐month follow up was 67% (106/158), and the recurrence rate was 31% (33/106). Independent predictors of ulcer‐free survival days were duration of diabetes, peripheral artery disease (PAD), cardiovascular disease, end‐stage renal disease (ESRD), and infection. Ulcer‐free survival days are related to PAD and cardiovascular disease, and ulcer‐free survival days should be the main outcome when comparing the effectiveness of management and prevention of the diabetic foot ulcers.